2011
DOI: 10.1002/jobm.201100048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbon source on polysaccharide production by alginate‐entrapped Aureobasidium pullulans ATCC 42023 cells

Abstract: The production of the exopolysaccharide pullulan using entrapped cells of the fungus Aureobasidium pullulans ATCC 42023 was investigated relative to carbon source. Fungal cells grown on glucose or sucrose as a carbon source were entrapped in calcium alginate beads and found to be capable of synthesizing the polysaccharide for two production cycles. Using 2.5% glucose or sucrose as a carbon source, productivity was 18.3 or 21.9 mg polysaccharide/g cells × h, respectively after the initial production cycle and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
(35 reference statements)
3
4
0
Order By: Relevance
“…Results of growth experiments revealed that maximum EPS were present in the cultures during late linear phase of growth and rate of maximum EPS production was also during this phase. Similar observations have been made by other workers on different microorganisms [15][16][17][18][19].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Results of growth experiments revealed that maximum EPS were present in the cultures during late linear phase of growth and rate of maximum EPS production was also during this phase. Similar observations have been made by other workers on different microorganisms [15][16][17][18][19].…”
Section: Discussionsupporting
confidence: 91%
“…Results of growth experiments revealed that maximum EPS were present in the cultures during late linear phase of growth and rate of maximum EPS production was also during this phase. Similar observations have been made by other workers on different microorganisms . Continued rate of EPS production during active growth of the organism suggests that it is a suitable candidate for continued EPS production in continuous cultures.…”
Section: Discussionsupporting
confidence: 88%
“…Maximum EPS production occurred in the cultures in stationary phase. Similar results have been seen previously [41][42][43]. In another study, production of a large amount of EPS was observed during late exponential or stationary phase growth in various cyanobacterial strains [44,45].…”
Section: Strainssupporting
confidence: 88%
“…However, the flocculant production and activity efficiency slightly reduced at highly acidic medium (pH<6) and highly alkaline medium (pH>9). Environmental conditions such as light intensity, temperature, culture medium, growth stage or nutrient availability affect the composition and quantity of EPS [19]; [20]. pH of the culture medium is important for cell growth and EPS production, perhaps relating to its influences on nutrient solubility and uptake, enzymatic activity, cell membrane morphology, byproduct formation and redox reactions [21][22][23][24][25], The flocculating activity of MMF1 isolated from the screening medium was 82.9% [26] which can be compared with present studied strains.…”
Section: Eps Characterization and Flocculating Activitymentioning
confidence: 99%